Power System Resilience Assessment Considering of Integrated Natural Gas System - Zhang, Huajun (2017)
Power system and natural gas (NG) system are two critical infrastructures (CI) that modern society depends on. The power system designed with conventional reliability criterion can neither effectively anticipate nor respond to high impact, low probability (HILP) events such as earthquake. At the same time, increasingly utilization of NG for electricity generation leads to rising intersystem coupling of power system and NG system. The interdependence imposes power system potential risk, such as failure propagation trigged by gas network contingency. Taken together with power system intrinsic complexity, these factors could operate to amplify disruptive effects. In this context, this paper aims to develop an effective model and approach to assess power system resilience considering associated fuel supply system based on two performance metrics: Expected Demand Not Supplied (EDNS) and Probability of Load Curtailments (PLC). It develops models of NG system, power system and their interdependence for quantitative measurement purpose, and generates an integral simulation frame using Non-sequential Monte Carlo simulation. Finally, it conducts case studies on modified Belgian gas transmission system and IEEE-24 reliability test system to justify the validity of the proposed approach.